The Influence Machine: A Commentary on Hähnel and Martensen (2019) - Shanahan, Daniel (Empirical Musicology Review, 2019)
This commentary discusses and contextualizes Hähnel and Martensen's analysis of Edison's recordings and correspondence, situating their study within some of the work done on the diffusion of innovations, and some other work on the history of recording. Their findings–that the mechanical limitations of recording possibly contributed to Edison's distaste for vocal vibrato–is mirrored in much of the work on early instrumental recordings, but whereas the effect for instrumental recordings was an increased vibrato, the solution for vocal recordings was the opposite.